Case Report: Invasive and Non-invasive Hemodynamic Assessment of Coronary Artery Disease: Strengths and Weaknesses - Gajanan, Ganesh; Samant, Saurabhi; Hovseth, Chad; Chatzizisis, Yiannis S. (Frontiers in Cardiovascular Medicine, 2022)
Coronary angiography has been the gold standard for assessment of coronary artery disease (CAD) and guidance for percutaneous coronary interventions (PCI). Physiology–guided PCI has shown increased safety and efficacy, improved resource utilization, and better clinical outcomes in patients with stable angina and acute coronary syndromes. The three cases presented and discussed in this report illustrate the strengths and weaknesses of the available invasive and noninvasive methods for the physiological assessment of CAD. As technology evolves, invasive non-wire-based (angiography-derived FFR) and noninvasive (FFRCT) modalities for the hemodynamic assessment of the CAD appear to provide reliable and user friendly alternatives to the gold standard invasive wire-based techniques. Interventional cardiologists and cardiovascular healthcare providers should be familiar with the strengths and weaknesses of the available hemodynamic assessment modalities.